2003
DOI: 10.1182/blood-2002-06-1768
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome inhibitor PS-341 potentiates sensitivity of multiple myeloma cells to conventional chemotherapeutic agents: therapeutic applications

Abstract: The proteasome inhibitor PS-341 inhibits nuclear factor-B (NF-B) activation, induces apoptosis in cancer cells, including multiple myeloma (MM) cells, and has marked clinical activity as a monotherapy for MM. In this study, we found that subtoxic concentrations of PS-341 potently sensitized MM cell lines and patient cells to DNAdamaging chemotherapeutic agents such as doxorubicin and melphalan, including cells resistant to these drugs and those isolated from a patient who had relapsed after PS-341 monotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
450
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(474 citation statements)
references
References 20 publications
23
450
0
1
Order By: Relevance
“…For example, it has been demonstrated that NF-kB inhibition with the proteasome PS-341 potentiates sensitivity of multiple myeloma cells to conventional cytotoxic drugs. In relation to these data, PS-341 has been administrated alone or in combination to other drugs in multiple myeloma patients, refractory to conventional therapies [19]. Similar results obtained with other NF-kB inhibitors have been described in ovarian cancer [20], in acute myeloid leukemia [8], and in other neoplasia.…”
Section: Discussionmentioning
confidence: 65%
“…For example, it has been demonstrated that NF-kB inhibition with the proteasome PS-341 potentiates sensitivity of multiple myeloma cells to conventional cytotoxic drugs. In relation to these data, PS-341 has been administrated alone or in combination to other drugs in multiple myeloma patients, refractory to conventional therapies [19]. Similar results obtained with other NF-kB inhibitors have been described in ovarian cancer [20], in acute myeloid leukemia [8], and in other neoplasia.…”
Section: Discussionmentioning
confidence: 65%
“…Microarray experiments have demonstrated that the transcriptional profile of a potentially large number of genes is changed in response to proteasome inhibition [6,[47][48][49], however, only in a few instances transcriptional profiling was complemented with the analysis of changes instigated within the proteome of the treated cells [6,50]. In the present study we therefore compared the subproteome of cells induced to undergo apoptosis by treatment with the proteasome inhibitor PSI with the subproteome of control cells using a high throughput immunoblot screening procedure and attempted to define changes relevant for the regulation of apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other changes such as the upregulation of various kinases (Btk, C-Raf, CK1e, GSK3b, IKKγ, ILK, Lyn, MEK5, PI3K p110d, PKAc, PKB, PKCa, Yes, c-Cbl) and phosphatases (PP1, PP2C, PTP1C, CD45) had not been noted in previous proteomic studies [compare with 6,50], which could have been due to cell type-and reagent specific differences, since other cell types (multiple myeloma or megakaryoblastic leukemia cells) aand different proteasome inhibitors (bortezomib, MG-132-lactacystin) were investigated. In addition, the level of various proteins were modulated that are involved in cytoskeletal organization, potentially contributing to the morphological changes that are associated with apoptotic cell death (Annexin I, ABP280, AKAP149, CRP1, cdc42, DMPK, dystrobrevin, FLAP, MEK5a, PRK2/PAK2, Rac1, Rho, VASP).…”
Section: Modulated Expression Of Proteins During Proteasome Inhibitormentioning
confidence: 98%
See 1 more Smart Citation
“…Synergistic myeloma cell kill in vitro has been noted with the combination of melphalan and bortezomib (Ma et al, 2003;Mitsiades et al, 2003). Bortezomib, by inhibiting the proteasome, interferes with DNA repair pathways and inhibitors of apoptosis, thus sensitising cells to DNAdamaging agents such as melphalan.…”
Section: Melphalan With Proteasome Inhibitors and Imidsmentioning
confidence: 99%